Application of CD38 monoclonal antibody in kidney disease - Chen, Zhiyi; Xu, Qianchun; Shou, Zhangfei (Frontiers in Immunology, 2024)
CD38 antigen is a glycoprotein that found on the surface of several immune cells, and this property makes its monoclonal antibodies have the effect of targeted elimination of immune cells. Therefore, the CD38 monoclonal antibody (such as daratumumab, Isatuximab) becomes a new treatment option for membranous nephropathy, lupus nephritis, renal transplantation, and other refractory kidney diseases. This review summarizes the application of CD38 monoclonal antibodies in different kidney diseases and highlights future prospects.